Factors Influencing Students’ Intention to Use E-Learning in Zhanjiang, China - Zhang, Zhengju (Scholar: Human Sciences, 2025)
Purpose: This research examined the factors influencing students’ behavioral intention to use e-learning in Zhanjiang, China. In the digital age, e-learning is increasingly favored for its convenience, flexibility, and sustainability. Given the widespread use of e-learning in education, it is necessary to conduct an in-depth study to examine the factors that influence students’ use of e-learning. Research design, data, and methodology: The study started with a validity analysis using the Item-Objective Consistency Index (IOC) and a reliability analysis using Cronbach’s Alpha (n=30). Multiple linear regression analyses were then conducted to test whether the variables had a significant relationship. Afterward, a 12-week Strategic plan (SP) was implemented for 30 students, and a paired-sample t-test was conducted on the quantitative results before and after the SP to determine the changes in students’ behavioral intentions to use e-learning by implementing the Strategic plan. Results: This study verified that the six independent variables (Effort expectancy, Performance expectancy, Habit, facilitating conditions, Hedonic motivation, and social influence) significantly influence the dependent variable (Behavioral intention to use). Concurrently, the paired sample t-test comparing results demonstrated a statistically significant difference between the pre- and post-strategic plan phases regarding students’ behavioral intention to use e-learning. Conclusions: This study identifies and validates several key factors significantly influencing students’ behavioral intentions to use e-learning environments. In addition, this study provides a rich research opportunity and theoretical foundation for future in-depth exploration and analysis.